MANUSIA DAN PERILAKU EKONOMI PERSPEKTIF ISLAM: Studi Atas Pemikiran Taqiyuddin an-Nabhānī - Sulaiman, Sofyan; Aisyah, Siti (LPPM Universitas Islam Indragiri, 2025)
This article examines the concept of human nature and economic behavior in Islam according to Taqiyuddin an-Nabhānī. Unlike the homo economicus of neo-classical economics, Islam views humans as complex beings influenced by intellect (‘aql), instinct (ghāriẓah), and physical needs (ḥājah al-‘uḍhwiyyah), all of which are governed by aqīdah (creed). One’s mindset (mafāhīm) and attitude (nafsiyyah) reflect their belief system. An-Nabhānī emphasizes that belief in divine destiny does not negate human free will (ikhtiyār), but rather balances God's will, natural laws, and individual moral responsibility. He also outlines the concept of ownership: private, public, and state-owned—where public ownership must be managed for the benefit of society. According to An-Nabhānī, the ideal Islamic economic framework is built upon sharī‘ah and aqīdah, integrating social justice, ethical worship, and a balance between human effort and reliance on God (tawakkul).